Pengaruh Pengungkapan ERM Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan, Leverage, dan Profitabilitas Sebagai Variabel Kontrol - Arifah, Elli; Wirajaya, I Gede Ary (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p30, 2018)
Increasing firm value is important for company to mazximize the prosperity of shareholders.Firm value can be increased by disclosing of Enterprise Risk Management (ERM) . The purpose of this study was to determine the effect of ERM disclosure on firm value by controlling firm size,leverage, and profitability. This research was conducted on property, real estate and construction sector companies which is listed on Indonesia Stock Exchange in 2014 to 2016. The number of samples are 123 companies with purposive sampling method. The analysis technique used in this research is multiple linear regression. The results shows that ERM disclosures has a negative and significant effect on firm value by controlling the variables of firm size, leverage and profitability. The negative influence shows that ERM disclosures conducted by property, real estate and construction sector companies were captured as a bad news by investors in addition to this disclosure is still voluntary. Keywords : firm value, enterprise risk management, firm size, leverage, profitability